Fragmented QRS is associated with ventricular arrhythmias in heart failure patients: A systematic review and meta‐analysis. Issue 1 (11th November 2021) - Engstrom, Nathan; Dobson, Geoffrey; Ng, Kevin; Letson, Hayley
Abstract: Introduction: Many primary prevention heart failure (HF) patients with an implantable cardiac defibrillator (ICD) rarely experience life‐threatening ventricular arrhythmias (VA). New strategies are required to identify patients most at risk of VA and sudden cardiac death who would benefit from an ICD. One potential method is the detection of fragmented QRS (fQRS) on the electrocardiogram. The aim was to assess the predictive capacity of fQRS for VA and mortality in ischemic (ICM) and non‐ischemic cardiomyopathy (NICM) primary prevention HF patients. Methods and Results: A systematic review and meta‐analysis of studies examining fQRS in HF patients with or without an ICD who met primary prevention indications with reduced ejection fraction ≤40%. Outcome measures were VA (or appropriate ICD therapy) and all‐cause mortality. Ten studies involving 3885 patients were included for analysis. Most patients were male with non‐fQRS patients being significantly younger (−1.5[−2.66, −0.42], p = .03). Diabetes was more likely in fQRS patients (1.12[1.01, 1.25], p = .03) while non‐fQRS patients were 28% more likely to have a history of atrial fibrillation (0.82[0.67, 1.00], p = .05). Ventricular arrhythmias were significantly 1.5 times more likely in patients with fQRS (1.51[1.02, 2.25], p = .04). HF patients were 1.7 times more likely to die of any cause if fQRS was present (1.68[1.13, 2.52], p = .01). NICM patients with fQRS have a significant 2.6‐fold increased incidence of death compared with ICM patients (2.55[1.63, 3.98], p < .0001). Conclusion: fQRS is associated with VA and all‐cause mortality and may be a novel marker in the risk stratification of primary prevention HF patients indicated for ICD implantation.